Preparation And Characterization Of Activated Carbon From Oil Palm Trunk Fiber By Chemical Activation - Jamaludin, Amierul Hafiezam (Universiti Sains Malaysia, 2022)
Industrial activated carbon has been a favoured adsorbent for the removal of a variety of contaminants, but its relatively expensive cost has limited its broad application. As the commercial activated carbon produced from non-renewable and unsustainable resources, this situation led to study on the possible alternative and low-cost replacements on raw materials to produce activated carbon. Due to the extensive discharge of pollutants, activated carbon produced from biomass waste by various processing methods and conditions is gaining popularity as a promising adsorbent for ecological treatment. Methods of manufacturing activated carbon, the type of lignocellulosic biomass waste, and the interaction between adsorbent and adsorbate are essential elements that must be considered in order to develop an effective adsorbent. Oil Palm trunk fibre (OPTF) is one of the major oil palm biomass wastes with a high carbon content that can be used as a precursor to produce activated carbon (AC) by utilising phosphoric acid (H3PO4) that can be turned into activated carbon with a large surface area and porous structure. This project's objective is to investigate how the impregnation ratio (IR) of OPTF and H3PO4 affects the porosity development and surface area of AC. Various physiochemical parameters such as pH of adsorbent solution and amount of activated carbon used were investigated in a batch adsorption technique. aximum surface area (1521.9 m2/g) was found at IR of 2, which demonstrates a type IV isotherm, that is contains micropores and mesopores. At three different pH values of 4, 7, and 10, adsorption equilibrium isotherms for methyl orange (MO) adsorption onto the AC were collected and nonlinearly fitted using the Langmuir and Freundlich isotherm models, with the Langmuir isotherm providing a better fit. The absence of repulsive electrostatic interaction between the AC surface and MO can account for the greater adsorption capacity at lower pH. In addition, the removal efficiency was not significantly improved by increasing the amount of activated carbon.